The m6A modification regulates the composition of myofiber types in chicken skeletal muscle - Yanju Shan; Yifan Liu; Ming Zhang; Lichuan Pang; Gaige Ji; Xiaojun Ju; Yunjie Tu; Jingting Shu (Poultry Science)
As a widespread epigenetic RNA modification, N6-methyladenosine (m6A) plays essential regulatory roles in multiple biological processes. However, its function in maintaining and modulating myofiber-type properties remains largely unknown. To investigate the post-transcriptional modification underlying the myofiber type diversity in chicken skeletal muscle, we evaluated the m6A methylation levels of chicken skeletal muscles with different phenotypic traits, and profiled a transcriptome-wide m6A map in the oxidative and glycolytic skeletal muscles by methylated RNA immunoprecipitation sequencing (MeRIP-seq). Our results showed that the levels of m6A methylation in chicken skeletal muscles were closely related to the composition of myofiber types. The m6A methylation level of anterior latissimus dorsi (ALD, typical oxidative skeletal muscle) was the highest among the three muscles and significantly higher than that of the pectoralis major (PM, typical glycolytic skeletal muscle) (P<0.05). We found that about 24.77 % and 33.50 % of genes were modified by m6A methylation in the PM and ALD, respectively, and identified 6,530 and 9,965 m6A peaks, which were mainly located in the coding sequence (CDS) and stop codon. About 3.14 % of m6A modified genes showed significantly differential methylation levels between these two muscles. Intriguingly, the myofiber type-related genes, such as MYOT, TPM3, TPM1, PDK1, MBNL1, and MYH1G, showed differences in m6A methylation and mRNA expression. Further analysis revealed that the m6A methylation was positively correlated with gene expression homeostasis. It is exciting we found that the expression level of ALKBH5 mRNA and protein, was closely related to the composition of myofiber types. ALKBH5 over-expression could regulate the expression levels of genes related to muscle contraction and metabolism, including MYH1E, MYH1G, MYH7B, PDK1, and TPM1, suggesting the effect of ALKBH5 on the formation of myofiber-type properties in chicken skeletal muscle. Our results contribute to a better understanding of epigenetic factors involved in forming chicken myofiber-type properties and provide new targets for further investigation into chicken's growth development and meat quality.